Consequências da hiperbolicidade na dinâmica das funções - Dourado, Jeremias (2020)
In this work we concern about hyperbolicity and your consequences in the dynamics of diffeomorphisms acting on compact manifolds. We introduce Anosov and Partially hyperbolic diffeomorphisms, and from hyperbolicity we get some topological and ergodic properties as transitivity, mixing, density of stable and unstable manifolds, and weak ergodicity. The main results in this dissertation are from the article of Arbieto, Catalan and Nobili.